Building a Competitive Spirit through the Use of Quizizz as an ICT-Based Evaluation Tool in Islamic Education: A Study on Fiqh Learning - May Nur Hidayati Novita; Irma Suraya (At-Ta'lim : Media Informasi Pendidikan Islam, 2024)
ENGLISH: Building Competitive Spirit through the Use of Quizizz as an Information and Communication Technology (ICT) Based Evaluation in Islamic Education Learning Fiqh MaterialObjective: This study aims to explore using Quizizz as an information and communication technology (ICT) based evaluation tool in learning Islamic education Fiqh material and building students' competitive spirit. Methods: This research uses a qualitative approach. Data were collected through classroom observation, in-depth interviews, data analysis, data reduction, data presentation, and conclusion drawing. Results: Using Quizizz to evaluate Fiqh learning creates a more dynamic and competitive learning atmosphere. Students are more motivated to participate due to gamification features such as instant scores and leaderboards. Conclusion: Quizizz can be an innovative ICT-based evaluation tool in Fiqh learning, improving learning outcomes and building students' competitive spirit. Contribution: This research contributes as a recommendation to educators to use Quizizz as an interesting and effective evaluation alternative in in Islamic education learning Fiqh material.INDONESIAN: Membangun Semangat Kompetitif melalui Penggunaan Quizizz sebagai Evaluasi Berbasis Teknologi Informasi dan Komunikasi (TIK) pada Pembelajaran Pendidikan Agama Islam Materi FiqihTujuan: Penelitian ini bertujuan untuk mengeksplorasi penggunaan Quizizz sebagai alat evaluasi berbasis Teknologi Informasi dan Komunikasi (TIK) dalam pembelajaran Pendidikan Agama Islam materi Fiqih, dalam membangun semangat kompetitif siswa. Metode: Penelitian ini menggunakan pendekatan kualitatif. Data dikumpulkan melalui observasi kelas, wawancara mendalam, analisis data menggunakan reduksi data, penyajian data dan penarikan kesimpulan. Hasil: Penggunaan Quizizz dalam evaluasi pembelajaran Fiqih menciptakan suasana belajar yang lebih dinamis dan kompetitif. Siswa lebih termotivasi untuk berpartisipasi karena adanya fitur gamifikasi seperti skor instan dan papan peringkat. Kesimpulan: Quizizz dapat menjadi alat evaluasi berbasis TIK yang inovatif dalam pembelajaran Fiqih, tidak hanya meningkatkan hasil belajar tetapi juga membangun semangat kompetitif siswa. Kontribusi: Penelitian ini berkontribusi sebagai rekomendasi kepada pendidik untuk menggunakan Quizizz sebagai salah satu alternatif evaluasi yang menarik dan efektif dalam dalam Pembelajaran Pendidikan Agama Islam Materi Fiqih.